2014
DOI: 10.1111/lcrp.12050
|View full text |Cite
|
Sign up to set email alerts
|

Consistency and specificity in burglars who commit prolific residential burglary: Testing the core assumptions underpinning behavioural crime linkage

Abstract: Purpose. Behavioural crime linkage is underpinned by two assumptions: (a) that offenders exhibit some degree of consistency in the way they commit offences (their modus operandi [MO]); and, (b) that offenders can be differentiated on the basis of their offence behaviour. The majority of existing studies sample at most three crimes from an offender's series of detected crimes and do not examine whether patterns differ across offenders. Here, we examine patterns observed across the entire detected series of each… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 65 publications
0
20
0
2
Order By: Relevance
“…A final point that emerges from the results published in the qualitative literature (e.g., Bennett and Wright, ; Cromwell, Olson, and Avary, ; Nee and Meenaghan, ; Rengert and Wasilchick, ; Wright and Decker, ) and in recent quantitative studies (Bouhana, Johnson, and Porter, ; Townsley and Sidebottom, ) is that although certain features often seem to influence offender decision‐making, there is also clear variation across offenders in those factors. For example, in their interviews with burglars, Bennett and Wright () found that the presence of passers‐by deterred approximately one half of their sample either unconditionally or under some conditions, whereas the remaining half reported being undeterred by the presence of others.…”
Section: Introductionmentioning
confidence: 99%
“…A final point that emerges from the results published in the qualitative literature (e.g., Bennett and Wright, ; Cromwell, Olson, and Avary, ; Nee and Meenaghan, ; Rengert and Wasilchick, ; Wright and Decker, ) and in recent quantitative studies (Bouhana, Johnson, and Porter, ; Townsley and Sidebottom, ) is that although certain features often seem to influence offender decision‐making, there is also clear variation across offenders in those factors. For example, in their interviews with burglars, Bennett and Wright () found that the presence of passers‐by deterred approximately one half of their sample either unconditionally or under some conditions, whereas the remaining half reported being undeterred by the presence of others.…”
Section: Introductionmentioning
confidence: 99%
“…Burglary is associated with a range of negative consequences for burglary victims including loss of property and damage to one's home, emotional trauma, stressful hypervigiliance due to the violation of privacy, increased anxiety, depression, and fear of crime, and others. 1 Like all criminal offenses, there is substantial heterogeneity among burglary offenders in terms of their broader criminal career (Bouhana, Johnson, & Porter, 2014;Hargreaves & Francis, 2014;Shover, 1996), motivation for perpetrating burglary (Maguire, 1988;Wright, Logie, & Decker, 1995), geographic and temporal issues relating to burglary (Johnson, 2008;Johnson & Bowers, 2004;Kocsis & Irwin, 1998), and the association of burglary to other forms of crime (Fox & Farrington, 2012;Shover, 1996;Steffensmeier, Harris, & Painter-Davis, 2015). Thus, burglary can denote a one-off adolescent prank by a juvenile offender, an opportunistic offense by an offender enmeshed in an antisocial lifestyle, or a carefully planned instrumental crime 3 (Shover, 1973).…”
Section: Introductionmentioning
confidence: 99%
“…In terms of the former, offender geographical and temporal behaviour (the ICD and TP, respectively) demonstrated greater consistency, distinctiveness, and discrimination accuracy than MO behaviours. These findings are consistent with previous research on commercial burglary, residential burglary, and auto theft (e.g., Bennell & Jones, ; Bouhana et al ., ; Goodwill & Alison, ; Tonkin et al ., ). A variety of explanations have been proposed for this superior performance (see Bennell & Jones, ), including that an offender can exert greater control over decisions about where and when to commit a crime than she or he can over decisions about what to steal, whether violence is used, etc., which depend to some extent on situational characteristics at the crime scene.…”
Section: Discussionmentioning
confidence: 99%
“…Approximately 30 empirical studies have been published in the last 15–20 years that seek to test whether sufficient offender behavioural consistency and distinctiveness exist to allow linked crimes to be distinguished from unlinked crimes (referred to as discrimination accuracy hereafter). These studies support the existence of offender behavioural consistency and distinctiveness for some offenders, some of the time, in a range of person‐ and property‐oriented crimes, including commercial and residential burglary (e.g., Bennell & Jones, ; Bouhana et al ., ), commercial and personal robbery (Burrell, Bull, & Bond, ; Woodhams & Toye, ), arson (e.g., Santtila, Fritzon, & Tamelander, ), rape/sexual assault (e.g., Yokota, Fujita, Watanabe, Yoshimoto, & Wachi, ), homicide (e.g., Melnyk, Bennell, Gauthier, & Gauthier, ), and auto theft (e.g., Tonkin, Grant, & Bond, ).…”
Section: Introductionmentioning
confidence: 99%